The dragon prophecy the fourth adventure in the Kingdom of Fantasy - Stilton, Geronimo (Geronimo Stilton, 2012)
Princess Sterling sends the Dragon of the Rainbow and Scribblehopper to bring Geronimo Stilton back the the Kingdom of Fantasy, because he is the hero in the dragon prophecy who will find the stolen dragon egg and restore harmony to the kingdom.